Examination of Multiple Rice Varieties (Oryza sativa L.) to the Development of Leaf Blight Disease Caused by Curvularia oryzae - Harman Hamidson; Effendy Effendy; Wike Nurwita Dewi; Shervinia Dwi Ayundra (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2020)
Hamidson H, Effendy E, Dewi WN, Ayundra SD. 2020. Test of multiple rice varieties (Oryza sativa L.) to the development of leaf blight disease caused by curvularia oryzae. Jurnal Lahan Suboptimal : Journal of Suboptimal Lands 9(2): 109-116. Rice is the main food commodity in Indonesia, since the majority of Indonesian populations use rice as their staple food. One of the common diseases that attack rice plants is leaf blight caused by pathogenic Curvularia oryzae. The objective of this research was to determine the reaction of five varieties of rice resistance to diseases caused by Curvularia oryzae. This research was conducted at Experimental Research Station and Phytopathology Laboratory of the Departement of Plant Pest and Disease, Faculty of Agriculture, Sriwijaya University from August to December 2016. Randomized block design was applied in this experiment by using 5 treatments and 10 replications. The Results showed that the highest percentage of leaf blight disease occured in P3 (Inpari 30) by 22,36% and the lowest percentage was found in P5 (varieties IR 10) by 2,85%.